EP799 Intraoperative molecular analysis during interval cytoreduction of high-grade serous tubo-ovarian carcinoma to confirm necessity for visceral resection. (1st November 2019) - Beirne, JP; Laura, F; McArt, D; Harley, I; McCluggage, WG; Mullan, P
Abstract : Introduction/Background: Cytoreductive Surgery (CRS) to zero visible residual disease is the strongest independent predictor of survival in advanced ovarian cancer. High-grade serous(HGSC) is the commonest and most aggressive sub-type. Carcinogenesis begins in the distal fallopian tube (NFT), via serous tubal intraepithelial carcinoma (STIC). Management may be through CRS followed by Adjuvant Chemotherapy (ACT) or Neoadjuvant Chemotherapy (NACT) followed by Interval CRS. Determining active visceral disease versus chemotherapeutic effect can be challenging during Interval CRS. A proportion of patients may be inappropriately treated and, therefore, potentially have worse survival or increased morbidity. Tumour-specific molecular alterations in surgical margins can predict risk of local recurrence. However, these assays are time-consuming and cannot be used in the intraoperative setting. The objective of this study was to validate tumour-specific methylated DNA assays using that could be used intra-operatively to assess sites of equivocal visceral disease in HGSC patients treated with NACT. Methodology: Six cases of HGSC were identified through the Northern Ireland Gynaecological Cancer Centre. Formalin-fixed paraffin embedded (FFPE) tissue samples were retrieved via the Northern Ireland Biobank (NIB11:005, NIB13:0094). Matched NFT and HGSC samples were analysed by DNA methylation (DNAme) array profiling. Bioinformatic analyses revealed hypermethylation of multiple loci in HGSC compared to NFT. The top differentially methylated targets were further validated in a second cohort using pyrosequencing and qMSP. Results: The top differentially methylated DNAme targets were analysed. Four were further validated in a cohort of 48 NFT and 48 HGSC unmatched samples. Pyrosequencing analysis revealed statistically significant differences (p< 0.0001) between each cohort with higher methylation in HGSC. A qMSP approach confirmed statistically significant (p< 0.0001) hypermethylation in HGSC compared to NFT samples. Conclusion: Intra-operative tissue biopsy analysis, using qMSP, is technically feasible. This technology may provide a more accurate tool to identify viable, residual HGSC following NACT and therefore assist with more appropriate CRS. Disclosure: Nothing to disclose.